2022
DOI: 10.1038/s41598-022-21554-0
|View full text |Cite
|
Sign up to set email alerts
|

Emotional prosody recognition enhances and progressively complexifies from childhood to adolescence

Abstract: Emotional prosody results from the dynamic variation of language’s acoustic non-verbal aspects that allow people to convey and recognize emotions. The goal of this paper is to understand how this recognition develops from childhood to adolescence. We also aim to investigate how the ability to perceive multiple emotions in the voice matures over time. We tested 133 children and adolescents, aged between 6 and 17 years old, exposed to 4 kinds of linguistically meaningless emotional (anger, fear, happiness, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Moreover, this effect of emotional messages in written speeches is in line with previous studies on charisma which investigated features of emotional messages such as choice of topic and 1 st person pronoun density (Gardner 2003;Rosenberg and Hirschberg 2009). Taken together, these findings suggest that speakers' oral delivery of a message may in fact distract listeners' focus from a potentially emotional message content (Wong 2001), with emotions being recognised in voice prosody without the processing of semantic information (Filippa et al 2022) Finally, emotionally arousing content words did not interact with message modality (Hypothesis 2b). This finding is somewhat surprising, given existing evidence that stimulus modality impacts on physiological arousal (e.g.…”
Section: The Moderating Effect Of Modalitysupporting
confidence: 88%
“…Moreover, this effect of emotional messages in written speeches is in line with previous studies on charisma which investigated features of emotional messages such as choice of topic and 1 st person pronoun density (Gardner 2003;Rosenberg and Hirschberg 2009). Taken together, these findings suggest that speakers' oral delivery of a message may in fact distract listeners' focus from a potentially emotional message content (Wong 2001), with emotions being recognised in voice prosody without the processing of semantic information (Filippa et al 2022) Finally, emotionally arousing content words did not interact with message modality (Hypothesis 2b). This finding is somewhat surprising, given existing evidence that stimulus modality impacts on physiological arousal (e.g.…”
Section: The Moderating Effect Of Modalitysupporting
confidence: 88%
“…Changes in the vocal output are one of these physiological changes observed during shifting emotional states. Although anger and happiness are relatively more recognizable (Filippa et al, 2022), several studies have repeatedly shown that a wide range of emotions are systematically embodied in the human voice, allowing individuals to communicate and/or recognize emotional experiences.…”
Section: Effect Of Emotional and Cognitive Load On Voicementioning
confidence: 99%